Teacher Competence: The Effect of Economic Welfare, Training and Achievement Motivation as an Intervening Variable - Agussalim; Sukardi; Muhammad Iqbal; Irwansya; Irmansah; Huzain Jailani (Dinamika Pendidikan, 2024)
The aim of this research is to analyze and describe the influence of economic prosperity and training on teacher competence through achievement motivation as an intervening variable. This research is a quantitative research with a research population of 320 public high school teachers in Bima City, and a research sample of 97 teachers. The instrument of this research is a questionnaire and was developed from each research variable. Data were analyzed using Structural Equation Modeling (SEM) analysis with the Partial Least Square (PLS4) method. The results of the research show that directly or intervened by achievement motivation, economic prosperity does not have a significant influence on teacher competence. Meanwhile, training, whether direct or intervened by achievement motivation, has a positive and significant influence on teacher competence. In conclusion, the more intense and relevant the training activities and the higher the teacher's achievement motivation, the higher the teacher's competence. Therefore, the development of teacher competency is prioritized by training based on the results of problem analysis and the need for teacher competency development as well as increasing achievement motivation.